Secularization and Islamic Education Maintaining Religious Identity at Madrasah Ibtidaiyah Miftahul Ulum Trimoharjo Bantul - Eka Lindayati; Hasan Asy’ari; Eva Sunarya; Hilmin Hilmin (Lembaga Yasin AlSys, 2026)
Amid globalization-induced secularization, Indonesian madrasahs such as MI Miftahul Ulum Trimoharjo face growing challenges in preserving students’ religious identity while integrating a national STEM-focused curriculum. Grounded in Berger’s secularization theory, Tajfel and Turner’s social identity theory, and al-Attas’s ta’dīb framework, this qualitative single-case study examines the impact of secularization on religious identity and the counterstrategies deployed at the institutional level. Data were generated through semi-structured interviews, observations, and document analysis involving the headmaster, Islamic education (PAI) teachers, and students, and were thematically analyzed following Braun and Clarke (2006), with trustworthiness ensured via triangulation and member checking. The findings reveal that secularization contributes to the erosion of tawḥīd-based values; however, the madrasah actively resists this trend through curriculum integration (e.g., infusing Islamic ethics into mathematics and science), daily worship habituation, Qur’anic literacy programs, teacher exemplarity, and structured partnerships with parents and the wider community. These strategies collectively foster improved religious awareness, discipline, and tajwīd performance, despite persistent gaps in teacher competency and variable levels of participation. Theoretically, the study enriches resilience models for Islamic education by illustrating how doctrinal, pedagogical, and communal resources can be mobilized to sustain religious identity under modernizing pressures. Practically, it offers contextually grounded and replicable strategies for similar institutions seeking to balance curricular modernization with robust Islamic formation. Acknowledging the limitations of its single-case design, the study points to the need for future multi-site and comparative research to deepen understanding of institutional responses to secularization in diverse Islamic educational settings.